Beneath the surface: unravelling a frontal epidermoid cyst–a case study - M. Jamali, Arwa; Luhana, Rakeshkumar (International Journal of Research in Medical Sciences, 2025)
Epidermoid cysts are rare, benign congenital lesions that account for a small percentage (0.3–1.8%) of primary intracranial tumors. These cysts arise from ectodermal cells that become trapped during the early closure of the neural tube in embryonic development. But their occurrence in the frontal lobe is extremely rare, with about 20 cases reported in literature. A 42-year-old male with a history of hypertension presented with generalized tonic-clonic seizures. magnetic resonance imaging (MRI) of the brain revealed a right frontal lobe lesion with mass effect, characterized as a non-enhancing intra-axial lesion. This imaging led to a preoperative diagnosis of low-grade glioma. The patient underwent a right frontal craniotomy with total microsurgical excision of the lesion and duroplasty under general anesthesia. Histopathological analysis of the lesion confirmed it to be an epidermoid cyst. Intracerebral epidermoid cysts, especially those located in the frontal lobe, are exceedingly rare and pose diagnostic challenges due to their similarity to more common brain lesions such as gliomas. Advanced imaging techniques, particularly diffusion-weighted MRI, are crucial in differentiating these cysts from other intracerebral tumors. Complete surgical resection is the definitive treatment, effectively preventing recurrence. The rarity of frontal lobe epidermoid cysts underscores the importance of thorough diagnostic and surgical strategies in managing this unique case.